2020
DOI: 10.26905/afr.v3i1.4555
|View full text |Cite
|
Sign up to set email alerts
|

Loan Loss Provision, Good Corporate Governance Dan Manajemen Laba Bank di Indonesia dan Malaysia

Abstract: The development of the banking sector in Indonesia and Malaysia is growing rapidly, fierce business competition encourages management's desire to improve performance and comply with banking regulations with earnings management reported by banks. The aimed of this study provides empirical evidence of the influence of Loan Loss Provision (LLP) and Good Corporate Governance (GCG) on Earnings Management in banks in Indonesia and Malaysia. The research method used is multiple linear regression analysis using a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…As a result of the implementation of IFRS standards, earnings management practices decreased (Dimitropoulos et al, 2013). Banks in Malaysia tend not to adopt a Loan Loss Provision (LLP) policy for income smoothing purposes, where they assume that during good economic times customers are able to pay their financing and in bad economic times, they tend to reserve a little for LLP (N. K. Sari & Widaninggar, 2020). Additionally, the mechanism for implementing good corporate governance (GCG) in these three countries can also discourage earnings management practices (Suripto, 2022).…”
Section: Effect Of Earnings Management On Bank Stabilitymentioning
confidence: 99%
“…As a result of the implementation of IFRS standards, earnings management practices decreased (Dimitropoulos et al, 2013). Banks in Malaysia tend not to adopt a Loan Loss Provision (LLP) policy for income smoothing purposes, where they assume that during good economic times customers are able to pay their financing and in bad economic times, they tend to reserve a little for LLP (N. K. Sari & Widaninggar, 2020). Additionally, the mechanism for implementing good corporate governance (GCG) in these three countries can also discourage earnings management practices (Suripto, 2022).…”
Section: Effect Of Earnings Management On Bank Stabilitymentioning
confidence: 99%
“…Positive accounting theory is designed to explain and predict which methods companies will use in their accounting practices (Watts and Zimmerman, 1986). Scott (2009) adds that TAP is used to explain the reasons for an accounting practice used by a company.…”
Section: Positive Accounting Theory (Tap)mentioning
confidence: 99%
“…In the banking industry the rules regarding reserves for impairment losses or Loan Loss Provisions (LLP) is very important in strengthening the financial position of the bank. LLP assists bank managers in dealing with future declines in credit quality (Sari and Widaninggar, 2021). In several research results (Abaoub and Gamra, 2013;Di Martino et al, 2017;Sari and Widaninggar, 2020) it was found that LLP is used by bank managers in managing earnings in various countries, because the determination of LLP uses direct judgment by bank managers which is dominated by higher in subjectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Manajemen dapat menentukan basis manajemen laba untuk memenuhi kepentingannya. Menurut Octavia (2017), manajemen laba dapat dilakukan melalui manipulasi akrual dan manipulasi dari aktivitas riil (Putra, 2014;Rukmana, 2018;Asim & Ismail, 2019;Widya & Nugrahani, 2018;Septriyani & Handayani, 2018;Sari & Widaninggar, 2020;Dewi & Anisykurlillah, 2021;dan Hasanuddin et al, 2021).…”
Section: Pendahuluanunclassified